2009
DOI: 10.1007/s00417-009-1248-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gestational age on the dynamic behavior of other risk factors associated with retinopathy of prematurity (ROP)

Abstract: BackgroundImproved survival of preterm neonates has increased the incidence of retinopathy of prematurity (ROP) in many middle-income countries.AimThis study aimed to verify the main risk factors for the development of ROP according to different gestational age (GA) groups.MethodsA prospective cohort study including infants weighing ≤1,500 g or GA ≤32 weeks at birth was conducted. The main clinical outcomes were the occurrence of any stage of ROP and severe ROP. The perinatal variables considered for the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
1
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 35 publications
4
20
1
11
Order By: Relevance
“…Although there was increased incidence of ROP in males in our study, this was not found to be significant ( P = 0.425). Similar non‐significant differences have been seen in other studies 4,18,26,27 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although there was increased incidence of ROP in males in our study, this was not found to be significant ( P = 0.425). Similar non‐significant differences have been seen in other studies 4,18,26,27 …”
Section: Discussionsupporting
confidence: 91%
“…Although it is difficult to make direct comparisons between studies in terms of specific incidence of ROP, consistent relationships between variables have been found. Population 5,13–15 and single‐centre studies 25–28 generally agree that with decreased GA and birthweight, there is increased frequency of ROP and increased incidence of severe ROP. Our findings are consistent with these trends, as seen in Figure 2 for birthweight and Table 4 for GA. Logistic regression analyses in this study revealed a strong inverse relationship between advancing GA and risk of development of ROP and severe ROP.…”
Section: Discussionmentioning
confidence: 96%
“…In a prospective cohort study by Fortes Filho et al,24 467 infants weighing ≤ 1500 g or gestational age ≤ 32 weeks at birth were divided into three groups according to gestational age: group 1, comprising infants of gestational age ≤ 28 weeks at birth; group 2, comprising infants of gestational age 29–31 weeks at birth; and group 3, comprising infants of gestational age ≥ 32 weeks at birth. Mean birth weight and gestational age in the total cohort was 1216.5 ± 278.3 g and 30.3 ± 2.2 weeks, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this analysis included every preterm infants who survived until treatment. Some studies only included preterm infants who survived at least 1 year 19 20. The risk for treatment decreased strongly for preterm infants with a GA of >25 weeks.…”
Section: Discussionmentioning
confidence: 99%